Effects of Electrical Stimulation of NAc Afferents on VP Neurons’ Tonic Firing - Clark, Martin (Frontiers in Cellular Neuroscience, 2020)
Afferents from the nucleus accumbens (NAc) are a major source of input into the ventral pallidum (VP). Research reveals that these afferents are GABAergic, however stimulation of these afferents induces both excitatory and inhibitory responses within the VP. These are likely to be partially mediated by enkephalin and substance P (SP), which are also released by these afferents, and are known to modulate VP neurons. However less is known about the potentially differential effects stimulation of these afferents has on subpopulations of neurons within the VP and the cellular mechanisms by which they exert their effects. The current study aimed to research this further using brain slices containing the VP, stimulation of the NAc afferents and multi-electrode array (MEA) recordings of their VP targets. Stimulation of the NAc afferents induced a pause in the tonic firing in 58% of the neurons studied in the VP, while 42% were not affected. Measures used to reveal electrophysiological difference between these groups found no significant differences in firing frequency, coefficient of variation and spike half-width. There was however significant differences in the pause duration between neurons in the dorsal and ventral VP, with stimulation of NAc afferents producing a significantly longer pause (0.48 ± 0.06 s) in tonic firing in dorsal VP neurons, compared to neurons in the ventral VP (0.21 ± 0.09 s). Pauses in the tonic firing of VP neurons, as a result of NAc afferent stimulation, were found to be largely mediated by GABAA receptors, as application of picrotoxin significantly reduced their duration. Opioid agonists and antagonists were found to have no significant effects on the pause in tonic activity induced by NAc afferent stimulation. However, NK-1 receptor antagonists caused significant decreases in the pause duration, suggesting that SP may contribute to the inhibitory effect of NAc afferent stimulation via activation of NK-1 receptors.